City waste for agriculture: emerging priorities which influence agenda setting. [Selected from the World Water Week, Stockholm, Sweden, 26-31 August 2012] - Raschid-Sally, Liqa (Elsevier, 2013)
Using city wastewater in agriculture for its water and nutrient values is a widespread practice that entails varying degrees of risk depending on the context of use. This paper presents the 'multiple realities' of wastewater use, describing the complex set of drivers that impels prevalent practices. These drivers in turn define a set of emerging issues and priorities. The paper emphasizes that recent thinking on the use of city water in agriculture has evolved rapidly, leading to gaps between the existing knowledge base and the knowledge needed to respond effectively and maximize benefits. In this paper we attempt to address these gaps by presenting a cross section of concepts, approaches and tools that are relevant to policy and can be utilized for agenda setting and good governance.